The dinosaurs next door - Castor, Harriet (Usborne Publishing Ltd, 2007)
The eccentric Mr. Puff lives next door to Sam in a house full of interesting things - including a basket of dinosaur eggs! When the dinosaurs begin to grow, something needs to be done - fast! An amusing, original story with easy reading text, speech bubbles and delightful illustrations on every page. Specially written as part of the Usborne Young Reading Programme for children who have just started reading alone.